2017
DOI: 10.1007/s12288-017-0849-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunohistochemistry, Cytochemistry, and Flow Cytometry in AML for Myeloperoxidase Detection

Abstract: Acute Myeloid Leukemia (AML) as per World Health Organization (WHO 2008) classification is on the basis of the antigenic characterization, enzymes restriction in the neoplastic myeloid cells and the specific translocations/mutations. AML can be assessed and differentiated by flowcytometry (FCM)/immunohistochemistry (IHC)/cytochemistry techniques. Myeloperoxidase (MPO) is an unequivocal marker to differentiate AML from the acute lymphoblastic leukemia. Despite FCM popularity, it has its limitations, in form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Therefore, the early diagnosis of leukemia for the treatment and the improvement of the quality of life of patients is essential. At present, the commonly used method for detecting leukemia is taking peripheral blood cells and bone marrow, after that many kinds of analysis [ 6 ], including cell morphology, cytochemistry [ 7 9 ], immunophenotype [ 10 , 11 ], immunohistochemical [ 12 , 13 ], and aptamer-based flow cytometry [ 14 , 15 ], have been carried out. These methods can detect leukemia cells, but they still have many shortcomings such as high cost, low sensitivity, and being complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the early diagnosis of leukemia for the treatment and the improvement of the quality of life of patients is essential. At present, the commonly used method for detecting leukemia is taking peripheral blood cells and bone marrow, after that many kinds of analysis [ 6 ], including cell morphology, cytochemistry [ 7 9 ], immunophenotype [ 10 , 11 ], immunohistochemical [ 12 , 13 ], and aptamer-based flow cytometry [ 14 , 15 ], have been carried out. These methods can detect leukemia cells, but they still have many shortcomings such as high cost, low sensitivity, and being complicated.…”
Section: Introductionmentioning
confidence: 99%
“…different protocols across participating centres) and limited correlations being reported by others. 4,[11][12][13][14] . Instead, two pairs of controls were selected, which were unfortunately not fully MPO negative or MPO positive.…”
Section: Discussionmentioning
confidence: 99%
“…relatively complex and expensive). [2][3][4] The UK National External Quality Assessment Service (NEQAS) has shown that standardisation of flow cytometric assays (at least in terms of dyes, clones and sample preparation) is crucial for reproducibility. 5 Nevertheless, to our best knowledge, no de facto standard or fully standardised flow cytometric assay exists for the MPO status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of a large number of neutrophils in alveolar cavity is one of the characteristic changes in ALI. The activity of myeloperoxidase (MPO), a redox marker enzyme in neutrophils, is used as an index of the accumulation of neutrophils in lung tissues [14]. Malondialdehyde (MDA) is a product of lipid peroxidation in cell membranes.…”
Section: Discussionmentioning
confidence: 99%